2013
DOI: 10.1186/1756-0500-6-41
|View full text |Cite
|
Sign up to set email alerts
|

Medical and biomedical research productivity from Palestine, 2002 – 2011

Abstract: BackgroundMedical research productivity reflects the level of medical education and practice in a particular country. The objective of this study was to examine the quantity and quality of medical and biomedical research published from Palestine.FindingsComprehensive review of the literature indexed by Scopus was conducted. Data from Jan 01, 2002 till December 31, 2011 was searched for authors affiliated with Palestine or Palestinian authority. Results were refined to limit the search to medical and biomedical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…We did not find any study similar to ours, thus we are unable to discuss this point in light of other results. However, some studies using the same tool for analysis have reported similar findings [5,10,29,30,32,33]. Countries with rapidly growing economies, which results in more funding and investments for research, contribute to the tendency of increasing number of toxicology publications such as KSA.…”
Section: Discussionmentioning
confidence: 75%
“…We did not find any study similar to ours, thus we are unable to discuss this point in light of other results. However, some studies using the same tool for analysis have reported similar findings [5,10,29,30,32,33]. Countries with rapidly growing economies, which results in more funding and investments for research, contribute to the tendency of increasing number of toxicology publications such as KSA.…”
Section: Discussionmentioning
confidence: 75%
“…Our study has few limitations related to nature of bibliometric studies (Sweileh et al 2013, 2014; Zyoud et al 2015a, b, c, d). False positive and false negative results are difficult to avoid regardless of how accurate the search stagey was.…”
Section: Discussionmentioning
confidence: 93%
“…This study is not without limitations, most of which are the same as those of studies performed in other biomedical fields [30,39]. First of all, we used Scopus criteria for including waterpipe-related keywords in our study.…”
Section: Discussionmentioning
confidence: 99%